374 THE INCIDENCE AND IMPLICATIONS OF CERVICAL SPINE ANOMALIES IN VELOCARDIOFACIAL SYNDROME. (1st January 2005) - Retallack, J.; Yong, S. L.; Bruce, A.; Reilly, C.; Loock, C.
Abstract : Purpose: Velocardiofacial syndrome (VCFS) is one of the most common causes of cleft palate. It is well established that patients with VCFS have anomalies of a number of cervical structures, such as the thymus and the parathyroid gland. However, the relationship of VCFS to anomalies of the cervical spine is not well recognized. Methods: In this case report and literature review, we discuss the incidence and implications of cervical spine anomalies in VCFS. A literature review of six articles o n cleft lip and palate, VCFS, Di George Syndrome, Spritzen Syndrome, and 22q11 deletion in association with musculoskeletal or cervical spine anomalies was completed. Two retrospective studies and one prospective study identified a total of 178 cases of VCFS. Results: The literature review confirmed a high incidence of cervical spine anomalies in patients with VCFS, ranging from 28–;55% patients. Of these patients, 8–;34% was symptomatic, presenting with cord compression, cranial nerve dysfunction, and hemiparesis. Cervical spine anomalies also have a direct effect on the dimensions of the pharynx and affect nasopharyngeal valve function. Velopharyngeal insufficiency (VPI) is common in VCFS, with an incidence of 27–;32%. VPI was previously attributed mainly to cleft palate, submucous cleft or palatal dysfunction. It is it now apparent that anomalies of the cervical spine can also cause VPI. Conclusion: Cervical spine anomalies are common and often under diagnosed in patients with VCFS. A high index of suspicion for these anomalies must be maintained, and cervical spine views in flexion and extension are recommended. Further imaging such as CT, MRI or angiography may be required as identification of cervical instability may require surgical management.